Histopathological effects of preoperative chemoradiotherapy for pancreatic cancer: An analysis for the impact of radiation and gemcitabine doses. Issue 1 (January 2015) - Hirata, Takero; Teshima, Teruki; Nishiyama, Kinji; Ogawa, Kazuhiko; Otani, Keisuke; Kawaguchi, Yoshifumi; Konishi, Koji; Tomita, Yasuhiko; Takahashi, Hidenori; Ohigashi, Hiroaki; Ishikawa, Osamu
Abstract Background and purpose Histopathological findings of patients who underwent resection for pancreatic adenocarcinoma (PC) after preoperative chemoradiotherapy (CRT) reportedly showed beneficial effects. The purpose of our study was to evaluate the correlation between histopathological effects (HE) of preoperative CRT and treatment parameters [radiation and gemcitabine (GEM) doses]. Material and methods HE of CRT were assessed on 158 primary lesions of 157 patients with PC who underwent pancreatic resection after preoperative CRT with GEM between January 2006 and December 2011. The radiation dose delivered to the primary tumor site and surrounding regional nodal areas was 50 Gy until September 2009 followed by the dose escalation of a 10 Gy boost added for delivery with the field-in-field technique to the roots of the celiac and superior mesenteric arteries. Intravenous administration of GEM (1000 mg/m2) was initiated concurrently on days 1, 8, and 15, every 4 weeks and generally repeated for 3 cycles. HE of CRT on the primary tumor were categorized based on the number of tumor cells destroyed. Results The median overall survival time was 74.5 months and 3-year and 5-year survival rates were 64.3% and 54.5%, respectively. Dose-volume parameters of radiation such as D33 with a cut-off value of 51.6 Gy were correlated significantly with HE (p = .0230). Lesions having received GEM > 7625 mg/m2 before surgical resection more frequently showed positive HE (p = .0002). Multivariate logistic regression analysis demonstrated that both D33 and cumulative GEM dose were significant predictors of definite HE (p = .0110 and <.0001, respectively). Conclusions Our retrospective analysis showed that dose intensity of radiation and GEM is significantly related to HE of preoperative CRT for PC.